If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 9 = 2 + 9x Reorder the terms: 9 + 2x = 2 + 9x Solving 9 + 2x = 2 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 9 + 2x + -9x = 2 + 9x + -9x Combine like terms: 2x + -9x = -7x 9 + -7x = 2 + 9x + -9x Combine like terms: 9x + -9x = 0 9 + -7x = 2 + 0 9 + -7x = 2 Add '-9' to each side of the equation. 9 + -9 + -7x = 2 + -9 Combine like terms: 9 + -9 = 0 0 + -7x = 2 + -9 -7x = 2 + -9 Combine like terms: 2 + -9 = -7 -7x = -7 Divide each side by '-7'. x = 1 Simplifying x = 1
| -20z+3=-19z+18 | | 8*20= | | -7x+25+2x=10 | | 56b-7=7+56b | | X^2+(-6x)=-9 | | 3y-1y+2y-5=7-2y+5 | | r/6=-2 | | sin50=x/21 | | 3(16x-24)+2= | | -13r+8r=10 | | 2(m+4)=8+2m | | 5x+8=98 | | 24+3x-6=9 | | .5b+7=22 | | -3x+5x-7=2(x-2)-5 | | -k-3=4-2k | | 5x+3=-x-27 | | 2+3r-4r=2 | | 10c-8/3-4c=6c | | e^0=x | | -13r-8r=10 | | 6h+8=5h | | (11x+4)=180 | | x^2-6x+y^2-4y-13=0 | | 6m(m+16)(m-13)=0 | | .25(8x+28)-19=-.40(30x-45) | | 10-7s=-3s-2s-10 | | 42=2x+6 | | 13x-(9+2(x+4))= | | -69-5x=3x+27 | | 1/1.75-2 | | -2-3y+2y=-13 |